Study of adolescent clinic: holistic approach for women health with dual client methodology - Shetty, Vishma H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The study is done to understand the gynaecological problems in adolescent girls. Do counseling, imparting knowledge for the girl and her mother, hence creating a holistic approach towards the women health in the family by dual client approach. Methods: 400 adolescent girls attending the clinic were studied (prospective observational study). Hb%, S.TSH was done for all the girls. Ultrasonography abdomen and pelvis was done on patient basis. Treatment was given. Mothers were counseled regarding their gynecological issues and screening tests (pap smear, self breast examination) was done after taking consent. Results: 70% girls had menstrual disturbances, 20% had complains of vaginal discharge. 44% had anemia (4% had severe anemia). Subclinical hypothyroidism was detected in 8% of cases. Ultrasonography was done in 52% of cases in which 81 patients had features suggestive of polycystic ovaries. 85.5% of the adolescent girls were accompanied by their mothers. 12% girls took HPV vaccination and 52% mothers underwent pap smear. Conclusions: Teenage problems need to be dealt very sensitively. Counseling is an integral component of treatment strategies. At present, adolescent gynaecology remains an area to which increased awareness and greater attention should be given to promote the health of teenagers and incult healthy lifestyle practices. In the same set up even the mothers of girls can be given counseling and address their gynaecological issues as majority of times mothers are the accompanying person creating the dual client approach in one setting. Hence adolescent clinic should aim for holistic, dual client approach for improvement of overall women health in the family.